Ecampus's Role in Supporting Learning in Higher Education - Zulfadli, Zulfadli; Khairat, Annisaul (ALSYSTECH Journal of Education Technology, 2023)
Technology plays an important role in supporting an education that can develop students' understanding. One platform that can be used as a learning medium is the E-Campus. This web application is often used by students and lecturers. In line with that the research is intended to find out the use of E-Campus as a learning medium for universities in the current era. This research was conducted using a quantitative method by conducting online surveys and in-depth interviews with students at various universities. The results of this study are the use of the ecampus web application in the learning process at various universities today, which is beneficial for a number of students and lecturers at tertiary institutions. To evaluate and understand ecampus in the learning process requires a deep understanding for students so they can use it properly. Therefore the limitation of this research is that the researcher did not make a design for using the e-campus in the study. The researcher hopes that further researchers can conduct research to build and develop this ecampus web application.